Strategic Manoeuvering in 2019 Campaign Speeches in the Eastern Cape Province in South Africa: Extended Pragma-Dialectical Perspective - Zameka Paula Sijadu; Gaspardus Mwombeki (Modern Africa, 2023)
This article investigates how political candidates in the Eastern Cape Province in South Africa employed means of strategic manoeuvring during the provincial election campaigns of 2019. It assumes the framework of the extended pragma-dialectical theory of argumentation, by first reconstructing the argumentation structure, identifying the means of strategic manoeuvring, and finally, critically analysing the prototypical speech acts in the political campaign discourse. The data were collected from the isiXhosa newspaper I’solezwe LesiXhosa during the campaign from February to April 2019. The findings demonstrate commissives and assertives as the prototypical speech acts in the political argumentative discourse in the Eastern Cape Province. In addition, dissociation is manifested in multiple contexts to persuade the audience of the standpoint that the opposition parties are more visionary than the incumbent party, African National Congress.